Study of complexes of platinum group metals containing nitrogen bases derived from pyridine aldehydes: Interesting molecular structures with unpredicted bonding modes of the ligands - Gupta, Gajendra; Gloria, Sairem; Nongbri, Saphidabha. L.; Therrien, Bruno; Rao, Kollipara Mohan (My University, 2011)
A series of mono-cationic dinuclear half sandwich ruthenium, rhodium and iridium metal complexes have been synthesized using ((pyridin-2-yl)methylimino)nicotinamide (L1) and ((picolinamido)phenyl)picolinamide (L2) ligands: [(η6-arene)2Ru2 (μ-L1)Cl3]+ (arene = C6H6, 1; p-iPrC6H4Me, 2; C6Me6, 3), [(η5-C5Me5)2M2(μ-L1)Cl3] + (M = Rh, 4; Ir, 5), and [(η6-arene)2Ru2(μ-L2)(μ-Cl)]+ (arene = C6H6, 6; p-iPrC6H4Me, 7; C6Me6, 8), [(η5-C5Me5)2M2(μ-L2)Cl2]+ (M = Rh, 9; Ir, 10). All the complexes have been isolated as their hexafluorophosphate salts and fully characterized by use of a combination of NMR and IR spectroscopy. The solid state structure of three representatives 4, 6 and 9 has been determined by X-ray crystallographic studies. Interestingly, in the molecular structure of 4, the first metal is bonded to two nitrogen atoms whereas the second metal center is coordinated to only one nitrogen atom with two terminal chloride ligands. Fascinatingly in the case of the complexes with the symmetrical ligand L2, both ruthenium centers having η6-arene groups are bonded to nitrogen atoms with a bridging chloride atom between the two metal centers, whereas the metals with η5-Cp∗ groups are bonded to the ligand N,O and N,N fashion.
Keywords: Arene ligands; Pyridine aldehydes; Schiff bases; Ruthenium; Rhodium and iridium